SEWAKA DHARMA AKTUALISASI PELAYANAN PUBLIK DI KOTA DENPASAR - Ni Luh Putu Ening Permini; I Kadek Dede Junaedy; Cok Gde Agung Kusuma Putra; Cokorda Putra Indrayana; Ni Kadek Ayu Dewi Purnama Sari; Wayan Aprilia Dwiyanti Saputri (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Bureaucratic reform is a demand, namely through innovation in public services. This is done to provide satisfaction to the community. Currently, technology and digitalization are important parts of people's social life. Technology directly changes people's mindsets to be more practical and responsive to existing phenomena. The problem is that the bureaucracy in providing public services tends to be slow in responding to technological developments. This study uses a qualitative approach, where data is obtained from observations and interviews. This study aims to discuss e-government-based public services related to their implementation so far, the suitability of the motto with the existing reality, the role of technology in public services and public administration studies. Denpasar City is one of the areas that tries to provide the best service to its people. Sewaka dharma is a motto which means serving is an obligation for bureaucrats and bureaucracy in the city of Denpasar. One of the steps is by implementing e-government as a way to bring and improve the performance of public services to the community. The result is that sewaka dharma as a motto for the obligation to serve for Denpasar city bureaucrats, is in accordance with the Nawa Cita concept upheld by the President of the Republic of Indonesia.